Lantana Camara Linnaeus : Profil Fitokimia dan Potensi Aktivitas Farmakologi - Intan Permata Putri; Irnawati Irnawati; Adryan Fristiohady; Sahidin; Muhammad Arba (Jurusan Farmasi Poltekkes kemenkes Makassar, 2026)
Lantana camara L. is a tropical plant from the Verbenaceae family that is widely known for its invasive nature, but also has high ethnomedicinal value. This study aims to examine the phytochemical profile and potential pharmacological activities of L. camara plants based on the latest scientific data. The study method uses a literature study approach to scientific literature from the Scopus database in the period 2015–2025 with keywords related to the phytochemistry and pharmacology of L. camara. The collected data were analyzed descriptively to identify the main bioactive compounds and their biological activities. The results of the study indicate that L. camara contains triterpenoids, flavonoids, phenolics, and iridoid glycosides that play an important role in various pharmacological activities, including antidiabetic, anticancer, antimicrobial, antioxidant, anti-inflammatory, and neuroprotective. Compounds such as ursolic acid, lantadene A and B, and quercetin-3-O-glucoside are reported to have significant biological effects through different molecular mechanisms. Furthermore, the potential use of L. camara in nanoparticle synthesis shows broad application prospects in the pharmaceutical and industrial fields. In conclusion, L. camara is a promising natural bioactive source for modern drug development and sustainable therapeutic applications.